PENGEMBANGAN MEDIA GAMBAR KARTUN MENGGUNAKAN APLIKASI PHOTOSHOP PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) KELAS VIII DI SMP NEGERI 1 TANJUANG BARU - octavia sisca; fetri yeni j (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
.Learning media by using cartoon images can be used as an alternative to reduce that problems in the learning process. Development of instructional media using cartoon images but can assist students in understanding the message delivered learning materials and is able to create an atmosphere of fun in learning. This study aims ti produce cartoons as a medium of learning media in accordance with the eligibility criteria and the media on the subject of Social Sciences (IPS) class VIII SMP Negeri 1 Tanjuang baru. Type of research is the development of research. Products developed through five phases: (1) Planning (2) Initial Product Development (3) Validation Products (4) Trial and (5) the product. Data collection tool was a questionnaire. Analysis descriptive data quantitatively to determine the quality of the product. The research model development is the procedural model with research subject 4 respondents, consisting of one validators media experts and one experts material ie 1 lectures UNP, and 1 teachers of Social Sciences (IPS) class VIII SMP Negeri 1 Tanjuang baru on the subjects of Social Sciences (IPS) CLASS VIII SMP Negeri 1 Tanjuang baru. Samples were VIIIgrade student at SMPN 1 Tanjuang baru on the subjects of Social Sciences (IPS). The validity of the test results for the material aspects of the media is in the category of “Very Good” by the percentage obtained by 82% and for aspects of the media is in the category of “Very Good” with a percentage 86% was obtained. Furthermore, in order to test the practicality of products based on the results of phase 2 trials that have been carried out in the category of “Very Good” by percentage gained 93%. This research results showed that the quality of media products developed cartoon as a whole is in the category of “Very Good” with a percentage of 92%. It can be concluded that the cartoon image of media products is feasible to be used in the learning process.